Untangling an AGS Outbreak Caused by the Recombinant GII.12[P16] Norovirus With Nanopore Sequencing - Xiong, Qianling; Jiang, Huimin; Liu, Zhe; Peng, Jinju; Sun, Jing; Fang, Ling; Li, Caixia; Qiu, Ming; Zhang, Xin; Lu, Jing (Frontiers in Cellular and Infection Microbiology, 2022)
For a rapidly spreading virus such as NoV (norovirus), pathogen identification, genotype classification, and transmission tracing are urgent for epidemic control. Here, we applied the Nanopore metatranscriptomic sequencing to determine the causative pathogen of a community AGS (Acute gastroenteritis) outbreak. The results were also confirmed by RT-PCR. The NGS (Next Generation Sequencing) library was constructed within 8 hours and sequence analyses were carried out in real-time. NoV positive reads were detected in 13 of 17 collected samples, including two water samples from sewage treatment tank and cistern. A nearly complete viral genome and other genome fragments could be generated from metatranscriptomic sequencing of 13 samples. The NoV sequences from water samples and cases are identical suggesting the potential source of the outbreak. The sequencing results also indicated the outbreak was likely caused by an emerging recombinant GII.12[P16] virus, which was only identified in the United States and Canada in 2017–2018. This is the first report of this emerging variant in mainland China, following the large outbreaks caused by the recombinant GII.17[P17] and GII.2[P16] in 2014 and 2016, respectively. Closely monitoring of the prevalence of this recombinant strain is required. Our data also highlighted the importance of real-time sequencing in emerging pathogens’ surveillance.